Estimating the aboveground biomass of Bornean Forest - Budiharta, S.; Raes, N.; Meijaard, E.; Erskine, P.D; Wilson, K.A.; Silk, J.W.F. (Wiley, 2014)
We apply a process‐based model, called 3‐PG (physiological principles for predicting growth), to estimate aboveground biomass for the primary forests of Borneo. Using publicly available soil and climate data, and parameterized with physiological traits of Bornean forest, the modeled aboveground biomass and basal area showed statistically significant relationships with field‐measured data from 85 sites across four major forest types. Our results highlight the possibility to expand the application of 3‐PG to forests of varying condition, which would facilitate inclusion of modeled forest biomass data for developing a Tier 3 carbon inventory system for Borneo.